Chican@ Artistic Practice: Performing Community in Contested Public Space - Raussert, Wilfried (Verbum et Lingua: Didáctica, lengua y cultura, 2020)
The article argues that it can be stated that Chican@ artistic practice has a strong affinity with community building. In this sense, Chican@ art practice holds a long tradition of seeking presence in public space in order to form, question and democratically promote communal bonding. The Chican@ art practice is largely hemispheric and refuses any national classification. In a cultural interspace between Mexican and American communities, Chican@ artists, musicians, and writers tend to engage in aesthetic and community-building cross-border projects. The article explores Chican@ performance culture from El Teatro de Campesino to contemporary border plays and performances of Guillermo Gómez-Peña and argues that artistic practices of Chican@ artists and activists have consciously sought to infiltrate public space and thus transform the public sphere through theater, art, and music in public settings.